Effect of powered activated carbon addition on substrate removal and sludge characteristics in leachate treatment - Kılıç, Emel. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2001., 2001)
The performance of activated sludge process depends on substrate removal efficiency and a good separation of biomass from the supernatant. Powdered Activated Carbon (PAC) addition to activated sludge is a promising method in the treatment of wastewater containing non-biodegradable and inhibitory substances. Substrate removal efficiency can be enhanced via addition of PAC to activated sludge systems in the treatment of leachate combined with domestic wastewater. The increase in substrate removal is due to adsorption of non-biodegradable and inhibitory and/or toxic compounds in the leachate. Moreover, addition of PAC has an effect on settling and dewatering characteristics of activated sludge. The purpose of this study was to investigate the effect of powdered activated carbon (PAC) addition on substrate removal and sludge characteristics in the cotreatment of leachate and domestic wastewater. In the first pali of the experimental path of the study, leachate and domestic wastewater were mixed at different ratios and PAC was added at various concentrations to batch reactors. Also, a control reactor was used which was fed under the same conditions as the PAC added reactor. Results showed that leachate could be treated successfully even if the leachate ratios was high (20-25 %) in the activated sludge system. The inert COD in PAC added activated sludge systems was lower than in activated sludge reactors. Results of the study also showed that the Specific Resistance to Filtration (SRF) increased during removal of readily biodegradable COD alld then tended to decline. Moreover, the SRFs of the sludges were higher if the leachate ratio increased. This showed that the dewaterability of the sludge decreased when the leachate ratio in the feed increased. As a general trend, in most of the runs, PAC addition suppressed these SRF increases. In the next step, leachate (diluted) and domestic wastewater were treated alone. The aim was to have an idea about the effect of leachate and domestic wastewater in the case of combined treatment. In the case of diluted leachate, although COD removal was considerable, sludge characteristics were negatively affected. PAC addition to leachate bad a positive effect. The effect of PAC was most obvious in the case of diluted leachate showing that leachate constituents were highly adsorbable onto activated carbon. The presence of domestic wastewater always resulted in a decrease in SRF or an increase in dewaterability. In the treatment of domestic wastewater alone, very high COD removal was observed and PAC addition did not result in additional COD removal. The SRF values of this sludge were much lower compared to leachate and co-treatment.
Keywords: Sewage -- Purification -- Activated sludge process.; Water -- Purification -- Adsorption.; Carbon, Activated.